FDI and Terrorism: An Analysis of the Impact of the Intifada on Foreign Direct Investment in the State of Israel - Glozer, Eyal (2006)
The natural flows of economic activities are often disturbed by political military exogenous events that cause the various economic activities to change course (Fishelson , 1993).Over the last century, such events have been dominated by religious fanaticism, ethnic nationalist conflicts and political ideologies, propelling a transnational phenomenon of international terrorism. This paper, using the Palestinian Israeli conflict ,Intifada, as such terrorist events, empirically elucidates, in accordance with a unique dataset on terrorism, the impact of terrorism on foreign direct investment into the state of Israel.